Between formal and hidden curriculum: Investigating dogmatism and exclusive ultranationalism among college students through content and participatory analysis - Yoga Ardian Feriandi; Risti Aulia Ulfah; Dwi Riyanti (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2026)
The rise of exclusive ultranationalism—manifested in xenophobia and intolerance—has become a growing concern among university students despite the mandatory implementation of civic education aimed at fostering inclusive citizenship. This study maps the risks posed by dogmatic narratives by examining the gap between the formal and hidden curricula in university civic education. Using a descriptive qualitative case study design, the research was conducted in teacher education programmes (PGSD/PGMI) at two Indonesian universities, with data collected through content analysis of curricular documents, non-participatory classroom observations, and in-depth interviews with lecturers and students. The findings reveal three systemic risks: monolithic content risk, where instructional materials emphasise cultural uniformity or a single religious interpretation; hidden curriculum risk, where pedagogical practices dominated by rote learning implicitly reinforce passive obedience and ideological exclusivity; and manifested vulnerability, observed in a minority of students who exhibit xenophobic reasoning and resistance to critical self-reflection. The study concludes that the emergence of exclusive ultranationalism is less driven by external ideological infiltration than by internal systemic weaknesses in civics pedagogy, highlighting the urgent need for pedagogical reform through the integration of critical pedagogy and the redesign of learning content to promote reflexivity, pluralism, and democratic citizenship.